Antioxidant, Antibacterial, and Antidiabetic Activities of Roselle (Hibiscus sabdariffa) Extracts - Lili Suharli; Baso Manguntungi; Andi Asmawati Azis; Apon Zaenal Mustopa; Lita Meilina; Iga Firmansyah Pandayu; Leggina Rezzy Vanggy; Shasmita Irawan (Annales Bogorienses, 2021)
Hibiscus sabdariffa L., also referred to as roselle, is commonly utilized in the pharmaceutical and food industries. Roselle contains bioactive compounds such as phenolics, alkaloids, tannins, flavonoids, saponins, and organic acids, which have pharmacological properties, such as antioxidant, antibacterial, immune booster, antidiabetic, anti-inflammatory, and anti-hypertensive properties. There are many studies regarding the pharmacological activities of roselle extract and its applications. However, there has been no research to study the effectiveness of the solvent in testing roselle petal extracts against antibacterial, antioxidant, and antidiabetic activities, simultaneously. This research used two kinds of polar solvents, dH2O and ethanol, with various concentrations for antibacterial activity test by five pathogenic bacteria, for antioxidant test by the DPPH method, and for antidiabetic test by the alpha-glucosidase inhibition method. The result showed that the ethanol extract of roselle had higher antibacterial activity compare to the roselle water extract. Antioxidant activity of roselle ethanol extract at 20% concentration had the highest activity 69.75 ± 0.002%; while, the 100% concentration of roselle water extract had the highest antioxidant activity 138.73 ± 0.013%. antidiabetic activity of roselle ethanol and water extract at 100% concentration had the highest activity 1,195.44 ± 0.007% and 1,552.49 ± 0.069%, respectively.